Initiatives to reduce nurses' Burnout during the COVID-19 pandemic: a scope review protocol (Research, Society and Development, 2022)
Objective: to map the available evidence on initiatives implemented to reduce the incidence of Burnout Syndrome among nurses who worked on the front line during the COVID-19 pandemic. Method: scope review protocol following the steps recommended by the Joanna Briggs Institute (JBI) and recommendations from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist, in the following databases: Embase, CINAHL, Cochrane, LILACS, MEDLINE/PubMed, Scopus, Web of Science and in the gray literature. The inclusion criteria will be primary studies, without language restrictions and available in full that answer the research question. In the selection stage, two reviewers will carry out this process with the support of Rayyan software. In case of discrepancies, a third reviewer will be summoned to assist in decision-making. The included studies will be presented through a summary table and narrative discussion. It is expected that the protocol generates the development of a scope review based on solid methodological procedures, producing results capable of contributing to effective strategies to reduce burnout in the nursing area, in view of the damage caused by the disease to affected professionals. The record of this review is in the Open Science Framework.